(untitled) (Web of Teachers: Inderscience Research, 2024)
This article publishes the results of the assessment of meat obtained from rabbits from a veterinary Sanitary Unit, the composition of which is carried out when rabbits being raised for meat are given the probiotic “Innoprovet”.